Volunteering Improves Employee Health and Organizational Outcomes Through Bonding With Coworkers and Enhanced Identification With Employers. Issue 5 (19th May 2022) - Pfeffer, Jeffrey; Singer, Sara; Stepanek, Martin
Abstract : Volunteers are healthier and more engaged than other employees, but the mechanisms underlying these associations are unclear. We found that volunteering works in part by increasing individuals' social bonding with each other and by enhancing their identification with their employers, with the greater social connection producing more positive outcomes. Abstract : Objective: To understand the consequences of employee volunteering and possible psychological mechanisms that produce these effects. Methods: Using data from more than 50, 000 responses to Britain's Healthiest Workplace survey, we employed structural equation modeling to investigate the effects of people volunteering. Results: Net of a number of controls, people who volunteered reported better self-reported health, less risk of depression, and higher levels of engagement and satisfaction. These results were partly explained by volunteering creating higher levels of interpersonal social bonding and greater identification with their employers. Conclusion: Employers Employers should sponsor volunteer activities and provide workplace flexibility, because employees who volunteer have greater individual wellbeing and also higher levels of pro-employer outcomes such as engagement and job satisfaction.